Interactive Effect of GA3, N and P Ameliorate Growth, Seed and Fibre Yield by Enhancing Photosynthetic Capacity and Carbonic Anhydrase Activity of Linseed: A Dual Purpose Crop - Mohammad N. Khan; Firoz Mohammad (Journal of Integrative Agriculture)
Linseed (Linum usitatissimum L.) is an important dual-purpose, industrial crop. Its seeds are used for the extraction of oil and stem for fibres. However, the production of linseed is not going parallel with the increasing demand of its products. The present work was carried out with an aim to find out whether exogenous application of gibberellic acid (GA3) with or without graded levels of nitrogen (N) and phosphorus (P) could improve the performance of three linseed genotypes Parvati, Shekhar and Shubhra together with minimizing the costly fertilizer input and losses. Four combinations of N and P, viz., 0 mg N+0 mg P kg−1 soil (N0P0), N13.4P4.46, N26.8P8.94 and N40.2P13.4 were constituted. Half dose of each combination was applied basally at the time of sowing and remaining half dose was given at 40 d after sowing (DAS) as foliar spray along with 10−6 mol L−1 GA3. Prior to sowing, the seeds of each linseed genotype were grouped in to two, one group of seeds was soaked in 0 mol L−1 GA3 (control) and the other group was soaked in 10−6 M GA3 solution, each for 8 hours. Treatments were comprised of (i) 0 mol L−1 GA3+N0P0 (T0, control), (ii) 10−6 mol L−1 GA3 + N134P446 (T1), (iii) 10−6 mol L−1 GA3+N26.8P8.94 (T2) and (iv) 10−6 mol L−1 GA3+N40.2P13.4 (T3). The crop performance was assessed in terms of growth, physiological and biochemical parameters at 60 and 75 DAS and yield attributes at harvest (175 DAS). The results showed a parallel increase in most of the parameters with increasing levels of N and P. However, application of 10−6 mol L−1 GA3 in association with N26.8P8.94 proved best, it enhanced seed yield, oil yield and fibre yield by 83.3, 97.3 and 78.7%, respectively accompanied with increase in net photosynthetic rate, carbonic anhydrase activity and dry matter accumulation. Among the genotypes tested, Shubhra performed best, while Parvati the least for most of the parameters studied. Thus, combined application of 10−6 mol L−1 GA3 plus N26.8P8.94 proved best and can be recommended to exploit the linseed as a dual-purpose crop for good yield of seed and fibre.